A comparative study on mica waste‐filled natural rubber foam composites made out of creamed and centrifuged latex. Issue 4 (3rd August 2022) - Dananjaya, Seekku Arachchige Vimukthi; Priyanka, Uhanowita Marage Shirani; Somarathna, Yashoda Ramyajith; Karunanayake, Laleen; Siriwardena, Susantha
Abstract: A comparative study on processed mica waste (PMW) filled natural rubber latex foams (NRLF) made out of centrifuged latex and creamed latex was conducted. The morphological, mechanical, and degradability properties of the composites were studied. The PMW was incorporated at 0, 2, 4, 6, 8, and 10 phr loading. Morphological studies revealed that both types of composites possess open‐cell structures. However, creamed latex based foam rubber composites showed foam structures with much larger cell sizes. PMW loading showed similar influences on the properties of the foam composites, irrespective of the latex type used. Increasing filler loading increases tensile strength, modulus at 100% elongation, tear strength, compression set, shrinkage, biodegradability, and antibacterial properties and reduces elongation at break and extractable protein content while offering a slightly dark color to the composites. It was also found that the creamed latex based foam rubber exhibits lesser extractable protein content and slightly inferior properties in tensile strength, shrinkage properties and color compared to centrifuged latex based foam rubber. However, it was shown that type of latex does not influence biodegradability, antibacterial properties, and color retention. Thermogravimetric analysis results confirmed the thermal resistance and reinforcing ability of mica in both NRLF composites. Abstract : Foam rubber were prepared using two types of concentrated latex namely centrifuged latex and creamed latex. Their degradability studies along with selected physio‐mechanical properties were investigated. It was found that foam rubber made out from Creamed latex possesses comparable properties to the foam rubber made out of centrifuged latex